1995
DOI: 10.1007/bf00224346
|View full text |Cite
|
Sign up to set email alerts
|

Variable degree of slime production is linked to different levels of beta-lactam susceptibility in Staphylococcus epidermidis phase variants

Abstract: Recently we demonstrated that lack of mecA transcription was responsible for the decreased methicillin resistance phenotype of strongly slime-negative Staphylococcus epidermidis phase variants [Mempel M, Feucht H, Ziehbuhr W, Endres M, Laufs R, Grüter L (1994) Antimicrob Agents Chemother 38: 1251-1255]. In the present study we compared the beta-lactam susceptibility and the slime production capacity of 60 phenotypic variants of S. epidermidis parent strain RP62A identified by their colony morphology on congo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The association between methicillin resistance and bioilm phenotype is taken atention according to studies executed [39][40][41]. Researchers determined that bioilm formation of HA- …”
Section: The Relationship Between Methicillin Resistance and Bioilm Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between methicillin resistance and bioilm phenotype is taken atention according to studies executed [39][40][41]. Researchers determined that bioilm formation of HA- …”
Section: The Relationship Between Methicillin Resistance and Bioilm Fmentioning
confidence: 99%
“…The association between methicillin resistance and bioilm phenotype is taken atention according to studies executed [39][40][41]. Researchers determined that bioilm formation of HA- MRSA BH1CC strain is decreased by removing SCCmec that results up-regulation of protease activity [4,42,43].…”
Section: The Relationship Between Methicillin Resistance and Bioilm Fmentioning
confidence: 99%
“…It therefore appears that more than one mechanism contributes to the production of phenotypic variants in S. epidermidis. In this context, it is interesting to note the reported association between the levels of resistance to methicillin, oxacillin, and penicillin and biofilm-forming capacity in phenotypic variants of S. epidermidis (45,46), suggesting that the phenotypic switch associated with impaired biofilm-forming capacity may also impact on other properties. In addition, the global regulators Agr and SarA, which influence methicillin resistance in S. aureus (50), have also been demonstrated to regulate staphylococcal biofilm formation (2,54,56,57).…”
mentioning
confidence: 99%
“…(54) recently reported that the staphylococcal accessory regulator, sarA, which controls the expression of over 100 genes (16), and not B was required for ica operon expression, PIA/PNAG synthesis, and biofilm development in S. aureus, although B was found to influence the regulation of ica operon transcription. In contrast, a transposon mutation in the rsbU gene in S. epidermidis was associated with both a reduction in PIA/PNAG levels and the loss of biofilm-forming capacity (32).Coagulase-negative staphylococci and S. aureus are capable of rapid phenotypic switching involving properties such as colony morphology, growth rate, antibiotic susceptibility, and biofilm-forming capacity (9,11,14,25,45,46,58,59). In terms of pathogenesis, staphylococcal phenotypic variation may contribute to dissemination, invasive disease, and sepsis.…”
mentioning
confidence: 99%
See 1 more Smart Citation